(untitled) (Jurnal Teknologi (Sciences & Engineering), 2017)
Fly ash is a by-product of coal burning and is widely used as a substitute for cement material. The advantages of using fly ash in concrete include the improvement of workability and reduction of bleeding and segregation. The problem often encountered when using fly ash is the uncertainty of the fly ash quality. The quality is influenced by the coal origin, burning technique, mineral content, and capturing method. In this study, the consistency of fly ash from one power plant source was investigated for making a high-volume fly ash (HVFA) mortar. Variations in fly ash can be detected by applying rapid indicators as suggested in this paper; i.e., the pH of the fly ash in aqueous solution, the percentage of fly ash particles passing sieve #325 and the superplasticizer demand for the targeted slump flow. The fly ash replacement ratio was varied from 10â€“60% of cement, by mass. The results showed a large variation in the chemical content of the fly ash as shown by variation in pH, whereas only slight variation in the physical properties of the fly ash, i.e. particle size and shape. Superplasticizer demand for the same flow diameter was reduced with the increase of fly ash content, whereas the optimum fly ash replacement ratio for maximum strength varied among fly ash from different sampling periods. The compressive strength could reach that of control specimens at a replacement ratio of 20â€“30%, and mortar compressive strength of 42Â MPa was still achievable at a replacement ratio of 50%.